Phase formation, microstructure, and dielectric properties of (1 - x)PZT-(x)PCN ceramics - Prasatkhetragarn A. (2014)
Ceramics in a PZT-PCN system with the formula (1 - x)Pb(Zr1/2Ti1/2)O3-(x)Pb(Co1/3Nb2/3)O3, where x = 0.0, 0.1, 0.2, 0.3, 0.4, 0.5, and 1.0, were prepared using a solid-state mixed-oxide technique with columbite-CoNb2O6 and wolframite-ZrTiO4 precursors. The crystal structure of the specimens studied with X-ray diffraction (XRD) analysis showed a coexistence between tetragonal and pseudo cubic phases at composition x = 0.2. The SEM micrograph showed that the average grain size significantly decreased with increasing PCN content. A maximum dielectric constant was observed at composition x = 0.2, while the transition temperature strongly decreased with increasing PCN content. All ceramics also showed diffused phase transition behaviors with a minimum diffusivity at x = 0.2. The morphotropic phase boundary (MPB) lay at the 0.8PZT-0.2PCN composition. © 2009 Elsevier B.V.